KEPASTIAN HUKUM PENYALURAN DAN KETERSEDIAAN BBM BERSUBSIDI UNTUK NELAYAN DI KECAMATAN SOROPIA, KABUPATEN KONAWE, SULAWESI TENGGARA - Wahyu Prianto (Prodi Ilmu Hukum, Universitas Teuku Umar, 2021)
Subsidized fuel oil (BBM) is the right of the poor in this country, including the small ones, BBM has an important role in increasing the productivity of fisheries, especially capture fisheries. The cost of using fuel in fisheries is up to 80% of the operational costs at sea. This is what makes BBM a strategic means of production for fishermen. The provision of adequate fuel, both in terms of quantity and price, is needed so that fishermen can use fuel according to their operational needs, this is the case with fishermen in Soropia District. The government's efforts to fulfill fishermen's rights through the policy of providing fuel subsidies have not worked as expected, the problem is that the small fishermen in Soropia sub-district, who are the targets of this fuel subsidy policy, do not enjoy it at all, the main thing is that the distribution patterns the government has taken so far are less effective, there are still many gaps that can be exploited by individuals to get benefits for themselves.This study aims to find the source of the problem of the obstruction of the distribution of subsidized fuel to small fishermen in Soropia Subdistrict, Konawe Regency and try to propose an operational pattern of distribution of subsidized fuel that is efficient, of course in accordance with legal provisions so that according to the title of this article is to provide protection of rights and legal certainty to Fishermen in Soropia District. The legal materials used consist of three types, the primary legal materials consist of all respondents (fishermen, the community and parties involved in the subsidized fuel oil distribution) regarding the distribution and use of subsidized fuel in Soropia sub-district, and combined with the perspective of legislation . whereas Legal Materials textbooks because textbooks contain basic principles of law science and classical views of highly qualified scholars. And Suber is an indication and explanation of primary and secondary legal materials. Collecting techniques through document studies or library materials and field studies, document studies are this activity aimed at obtaining data through tracing notes, writings or documents that have been made by other people related to the issues being discussed. Field studies are field observations with competent parties in order to obtain data information about the subject and object under study. The data used is to analyze the data obtained in accordance with the symptoms and objects that occur in the field and then summarize, select the main things, look for themes and patterns. The method of analysis of legal materials used is descriptive method. with this descriptive method, actual detailed information can be obtained.Based on the results of the research that the ineffective distribution and availability of subsidized fuel for fishermen in Soropia Subdistrict, Konawe Regency, Southeast Sulawesi, occurred due to several things, starting from Soropia Subdistrict, Konawe Regency, Southeast Sulawesi, the absence of Fishermen Solar Pack Dealer (SPDN), The sub-district fisherman card management for fishermen in the Soropia sub-district is that this problem is not taken care of in the Soropia sub-district itself, but has to take care of the main Konawe district, namely the Unaaha district and about how from a legal standpoint whether this fuel subsidy actually reaches fishermen, this is There is a game between the owners of Solar Pack Dealer Fishermen (SPDN) or brokers or subsidized fuel retailers, then the question is how to legally protect the rights of fishermen, especially the rights of fishermen in Soropia sub-district to distribute subsidized fuel